Textos escolares, saber pedagógico e infancia en el Ecuador (1930-1955) [Estudios] - Fernández Rueda, Sonia Marina (2024)
With the premise that emerged in the 1990s that school textbooks are a rich source of information for the study of a variety of new fields of research linked to the history of education, this article seeks to establish the relationship between school textbooks, pedagogical knowledge and childhood, with the aim of showing how school textbooks are not only designed to embrace new pedagogical ideas, but also harbor notions related to the collective imaginaries that appear from different spheres of society regaridng children.